1980
DOI: 10.1017/s0033291700044044
|View full text |Cite
|
Sign up to set email alerts
|

Parental death in childhood and risk of adult depressive disorders: a review

Abstract: SYNOPSISThe authors review the evidence that parental death in childhood predisposes to depressive disorders in later life. The findings in general are quite inconsistent; this is due in part to the methodological limitations of most studies, principally that of inadequate control of potentially confounding variables. Where experimental and control samples were most rigorously matched, no association was found between childhood parental bereavement and depression in later life. Parental death in childhood appe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
60
3
1

Year Published

1981
1981
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(64 citation statements)
references
References 45 publications
(71 reference statements)
0
60
3
1
Order By: Relevance
“…5 The parents of the adolescents in that study were vulnerable to drug abuse and poverty, which placed them at risk for depression, 4 conduct problems, and other risk factors. 6,7 We used the same study sample in an extension of the Rotheram-Borus study, to examine the affect of social support on adolescents' mental and behavioral outcomes. Adolescents in the intervention group reported significantly lower levels of emotional distress, fewer multiple problem behaviors, and fewer conduct problems.…”
Section: The Effect Of Social Support On Mental and Behavioral Outcommentioning
confidence: 99%
“…5 The parents of the adolescents in that study were vulnerable to drug abuse and poverty, which placed them at risk for depression, 4 conduct problems, and other risk factors. 6,7 We used the same study sample in an extension of the Rotheram-Borus study, to examine the affect of social support on adolescents' mental and behavioral outcomes. Adolescents in the intervention group reported significantly lower levels of emotional distress, fewer multiple problem behaviors, and fewer conduct problems.…”
Section: The Effect Of Social Support On Mental and Behavioral Outcommentioning
confidence: 99%
“…Freud's (1917Freud's ( /1950hypothesis that adult depression was associated with the loss of a parent or other loved object in childhood became widely accepted over the next 50 years and provided the rationale for making these discriminations. More recently, however, reviewers have concluded that most of the evidence does not support this hypothesis (Bifulco et al, 1987;Crook and Eliot, 1980;Tennant et al, 1980). Nevertheless, a number of other theories ranging from attachment to social learning to family systems also provide rationales for expecting lower family functioning in various clinical groups.…”
Section: Discriminant Validitymentioning
confidence: 99%
“…There is the considerable danger in controlling for certain of the more obvious and easily measurable variables, while neglecting subtle influences. Tennant, Bebbington, and Hurry (1980), in a recent review of studies related to depressive illness, accounted for factors commonly studied in epidemiological research but made only passing reference to the more psychological influences. They conveyed the impression that, with a little modification, early bereavement can be treated much like any other pathogen.…”
Section: Disenchantment With the Head-counting Approachmentioning
confidence: 99%